EFL Students’ Perception and Motivation Toward Quizizz as E-Learning Media in English E-Classroom - Farah Ika Dhamayanti (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
This study investigates the English as Foreign Language (EFL) students' perception and motivation toward Quizizz as e-learning media in English e-classroom. The total number of participants in this study is 106 students of 11th graders of Senior High School consist of five classes who had experience toward Quizizz. A descriptive statistics approach is applied in this study. The data collected by using closed-ended questionnaire. The obtained data were analyzed by using SPSS version 25.00. The result shows most of EFL students had positive perception and motivation toward Quizizz. Therefore, Quizizz as e-learning media can support the learning process in English e-classroom. It indicates that Quizizz is an appropriate e-learning media that can be used in English e-classroom and it can increase EFL students’ motivation during e-learning.